Pengembangan LKPD Edukatif Mitigasi Bencana Kebakaran sebagai Upaya Pencegahan Dini Kelas 3 Sekolah Dasar - Anastasia, Lucya; Valerian P.K, Sebastian; Akbar, Rheno Fadilah; Istiq’faroh, Nurul (CV. Kurnia Grup, 2026)
Fire disasters pose a serious threat that can occur at any time in the school environment, yet elementary school students generally lack adequate mitigation understanding and often experience panic during emergency situations. This research aims to develop educational Student Worksheets (LKPD) based on fire disaster mitigation as an interactive teaching material innovation for grade 3 elementary school students. The research method used is Research and Development (R&D) with the 4D development model consisting of the Define, Design, Develop, and Disseminate stages. The trial subjects in this study were 20 third-grade students of UPT SDN 233 Gresik. The results showed that the developed LKPD met the very feasible criteria with material expert validation percentage of 94.04% and media expert validation of 77.17%. Furthermore, the practicality level of the product is in the very high category, evidenced by teacher response questionnaire results of 96.8% and student responses of 94.8%. The conclusion of this study is that the educational game-based fire disaster mitigation LKPD is valid and very practical for use in learning. This product is effective in helping students understand safety procedures contextually through engaging learning experiences, thereby minimizing disaster risks from an early age.